PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA RUMAH MAKAN ZAM-ZAM - B31109010, Nova Mardiana Muntiastopo (Jurnal Manajemen Update, 2016)
This study was to examine and analyze the effect of product quality, service quality and price to customer satisfaction by the restaurant Zam-zam Pontianak. The study was designed as a descriptive survey research are used for describing the real situation objectively based in facts that appear or as they are both qualitative and quantitative. The population of this study was a sample of 100 consumers regulars at the restaurant Zam-zam who has bought third. The results showed that the results of the regression analysis between the quality of the product (X1) towards consumer satisfaction (Y) showed a significant value t (0,000) < 0,05. This shows a partial isÂ  there significant influence between product quality to customer satisfaction. The regression analysis between the quality of service (X2) towards consumer satisfaction (Y) showed a no significant value t (0,418) > 0,05.This shows a partial no significant influence between quality of service to customer satisfaction. The regression analysis between the price (X3) towards consumer satisfaction (Y) showed is there significant value t (0,045) < 0,05. This shows a partial is there significant influence between priceto customer satisfaction. Keywords : Pruduct Quality, Service Quality and Price.